The White House Looks South : Franklin D. Roosevelt, Harry S. Truman, Lyndon B. Johnson - Leuchtenburg, William E. (William Edward), 1922- (Book collections on Project MUSE., 2005)
Perhaps not southerners in the usual sense, Franklin D. Roosevelt, Harry S. Truman, and Lyndon B. Johnson each demonstrated a political style and philosophy that helped them influence the South and unite the country in ways that few other presidents have. Combining vivid biography and political insight, William E. Leuchtenburg offers an engaging account of relations between these three presidents and the South while also tracing how the region came to embrace a national perspective without losing its distinctive sense of place. According to Leuchtenburg, each man "had one foot below the Mason-D